Application of Project-Based Learning Methods to Improve Critical Thinking - Dara Nidia Cahyuni; Cindy Dwi Yunita; Delva Zakia Agustin; Revani Maya (Greenation Education and Culture Review, 2026)
The monotonous learning process and ignoring the active participation of students is one of the causes of low critical thinking skills. This study aims to describe the learning process using a project-based learning model and describe the improvement of critical thinking skills through its use. The method used is descriptive qualitative with a literature review approach. The Project-Based Learning Method (PBL) is implemented to help students think critically about the problem at hand. Project-Based Learning focuses on learning that exposes students to collaborative problems. These problems are unstructured, thus presenting unique challenges for students. When implemented in the classroom, students are required to be active and responsive to the problems presented. With PBL learning, students will remain motivated to continue learning and hone their problem-solving skills. The implementation of this method cannot be separated from positive and negative impacts. The positive impact is to help students process information better and help them learn to think critically when faced with problems. However, the negative impact generally arises from the fact that the implementation of this method requires high costs for teaching aids and the long time required from concept preparation to implementation.